An insight into the polymerization process of the selected carbazole derivatives - why does it not always lead to a polymer formation?. (10th October 2022) - Jyoti,; Dmitrieva, Evgenia; Żołek, Teresa; Maciejewska, Dorota; Rybakiewicz-Sekita, Renata; Kutner, Włodzimierz; Noworyta, Krzysztof R.
Highlights: Spectroelectrochemistry of two naphthalene-appended carbazole derivatives was studied. Dithienylated carbazole monomer is efficiently electropolymerized while non-thienylated is not. Quantum-chemistry calculations explained differences in monomers' electropolymerization. Cation radical delocalization limits electropolymerization of the non-thienylated monomer. Abstract: Among numerous monomers of carbazole derivatives, some reveal intriguing differences in their electrochemical polymerization behavior. Two such monomers, namely, 9-(2-naphthalen-2-yl)-9 H -carbazole, CNZ1, and 9-(naphthalen-2-yl)-3, 6-di(thiophen-2-yl)-9 H -carbazole, CNZ2, were herein studied to a greater detail. The main research focus was to elucidate the electropolymerization mechanism of both monomers. The monomers were electro-oxidized to form polymer films on electrodes. When CNZ1 and CNZ2 were electro-oxidized under the same conditions, the overall charge passed was 115 and 1500 µC, respectively, suggesting the formation of a very thin poly(CNZ1) film and, in contrast, a thick poly(CNZ2) film. The polymers electrochemically behaved reversibly at electrodes. They were characterized by a combined UV-vis-NIR and electron paramagnetic resonance (EPR) spectroelectrochemistry. The UV-vis-NIR absorption intensity for the poly(CNZ1) film was 10 times lower than for its monomer, but the poly(CNZ2) film behaved differently. The number of radicals formed in poly(CNZ1) during the electro-oxidation was ∼30 times lower than in poly(CNZ2) . We examined the formation of different charge carriers and their concentration evolution using in-situ spectroelectrochemical methods. Scanning electron microscopy (SEM) imaging revealed a continuous and granular morphology of poly(CNZ1) and poly(CNZ2) films, respectively. UV-vis-NIR and EPR spectroelectrochemistry coupled with quantum-chemistry calculations enabled us to shine more light on differences in the behavior observed. For CNZ1, the radical is delocalized over the whole molecule. That can lead to a lower reactivity, thus preventing the formation of long polymer chains. In contrast, the radical delocalization is much more restricted to the carbazole-thiophene moiety for CNZ2 . Consequently, this inccreased localization leads to the formation of long polymer chains. Graphical abstract: Image, graphical abstract